Making Claims that Matter: Heuristics for Theoretical and Social Impact in Qualitative Research. (October 2018) - Huffman, Tim; Tracy, Sarah J.
Scholar activists draw on a variety of theoretical, methodological, and practical tools for creating and sustaining social justice. We argue that data analysis—in addition to research design, participation, and community engagement—can be leveraged to engage in scholarship for social good. This essay contributes to that effort by offering a set of data analytic heuristic devices for qualitative researchers. These heuristic devices include community cocktail party, conjecturing claims, Jeopardy research questions, phronetic claims, carrying claims, and tightening claims. We outline each heuristic device's use, purpose, underlying philosophical commitments, and how it aids analytic thinking that serves the pursuit of justice. Using these devices provides opportunities for making claims that matter and strengthening the impact of qualitative research.